A study of out the relationship between social intelligence and academic achievement of college students - Anoop Singh; Dr. Shivkant Sharma (Innovative Research Thoughts, 2024)
In this study, researchers from Universiti Teknologi Mara's Education Faculty look at the connection between EQ and academic success (UiTM). With the use of a questionnaire designed to elicit information on the students' Emotional Intelligence level and academic achievement, this study was able to collect the data necessary for its analysis. Conclusion: Respondents exhibit high levels of Emotional Intelligence, according to the research. Academic success is revealed to be strongly and positively correlated with two sub-domains of Emotional Intelligence (Self-Emotion Appraisal and Understanding of Emotion). The study's results have significant implications for the significance of Emotional Intelligence and its linkages to students' academic achievement, particularly for in-training educators.